INTEGRITAS GURU SEKOLAH MENENGAH KEJURUAN (KAJIAN FENOMENOLOGI DALAM MENJAGA KOMITMEN PROFESI DI SMK PUSTEK SERPONG) - Mirah Paramitha; Siti Zubaidah; Rian Sri Rahayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of teacher integrity in maintaining professional commitment at SMK PUSTEK Serpong. The study employed a qualitative approach using a descriptive method and a phenomenological perspective to gain an in-depth understanding of teachers' subjective experiences in implementing professional integrity, particularly in carrying out their duties, responsibilities, and professional ethics within the school environment. The research was conducted at SMK PUSTEK Serpong, South Tangerang City. Data were collected through observation, in-depth interviews, documentation, and field notes. Data trustworthiness was ensured through source triangulation and method triangulation, while data analysis was carried out through the stages of data reduction, data presentation, coding, data interpretation, and conclusion drawing. The findings indicate that teacher integrity in maintaining professional commitment is not merely an individual characteristic but has evolved into a professional culture supported by moral values, the school organizational environment, harmonious interpersonal relationships, and supportive school leadership. These seven aspects of integrity are interconnected and form a value system that strengthens teachers' professional commitment. Therefore, integrity serves as the primary foundation for developing adaptive, ethical, and professional educators who are committed to continuously improving the quality of education.